The Path of AI Technology to Promote Sustainable Development of China’s Cultural Industry: An empirical analysis based on Digital Cultural Communication - Jiale, Tao (Indonesian Journal Publisher, 2025)
Artificial intelligence technology is currently reshaping the global cultural industry profoundly. This study uses Chinese digital cultural products as the cases, and adopts case analysis and phenomenological methods to explore how AI technology can promote the sustainable development of China’s cultural industry through content production, communication innovation and industrial upgrading. The study found that AI has formed a “technology-culture-market” synergy mechanism in the three dimensions of cultural digital protection, global communication and user interactive experience, but faces challenges such as technological ethics, cultural discounts and unequal resource allocation. Finally, a three-element development framework of “policy guidance-technology empowerment-ecological co-construction” is proposed.